1993
DOI: 10.1002/cne.903340308
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characteristics of fish glial fibrillary acidic protein: Implications for optic nerve regeneration

Abstract: Mammalian central nervous system neurons do not regenerate after axonal injury, unlike their counterparts in fish and amphibians. After axonal injury, glial cells in mammals do not support regrowth of axons, while in fish they support the regeneration process. Controversy exists as to whether or not the intact fish optic nerve expresses glial fibrillary acidic protein, a well-known marker for mature astrocytes, and thus whether its astrocytes differ in this respect from those of the brain and spinal cord, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…In the adult zebrafish, anti-gGFAP recognizes a major band of 51 kDa, which is consistent with other reports for the molecular weight of GFAP in fish (Quitschke et al, 1985;Maggs and Scholes, 1986;Levine, 1989;Nona et al, 1989). In addition, a second band was recognized at 45 kDa, which is consistent with other reports on fish (Dahl et al, 1985;Quitschke et al, 1985;Levine, 1989;Cohen et al, 1993). More than one form of GFAP has also been observed in Xenopus (Szaro and Gainer, 1986) and axolotl (Holder et al, 19901, and it has been suggested that GFAP may exist in more than one form in animals that retain radial glia throughout life (Holder et al, 1990).…”
Section: Discussion Gfap Expression In Fish Gliasupporting
confidence: 93%
“…In the adult zebrafish, anti-gGFAP recognizes a major band of 51 kDa, which is consistent with other reports for the molecular weight of GFAP in fish (Quitschke et al, 1985;Maggs and Scholes, 1986;Levine, 1989;Nona et al, 1989). In addition, a second band was recognized at 45 kDa, which is consistent with other reports on fish (Dahl et al, 1985;Quitschke et al, 1985;Levine, 1989;Cohen et al, 1993). More than one form of GFAP has also been observed in Xenopus (Szaro and Gainer, 1986) and axolotl (Holder et al, 19901, and it has been suggested that GFAP may exist in more than one form in animals that retain radial glia throughout life (Holder et al, 1990).…”
Section: Discussion Gfap Expression In Fish Gliasupporting
confidence: 93%
“…When excised and analyzed, the injury site is found to be devoid of astrocytes, as indicated by immunocytochemical staining with anti-GFAP antibodies (Fig. 1 a ) and by transmission electron microscopical analysis as was previously shown by Blaugrund et al (8,9) and by Cohen et al (10). To determine whether the relatively long-lasting absence of astrocytes at the injury site is related to the nature of the soluble substances associated with the injured nerve, we applied the optic nerve-derived soluble substances to a scratch wounded monolayer of astrocytes.…”
Section: Simulation Of the Postinjury In Vivo Behavior Of Astrocytes supporting
confidence: 71%
“…Thus for example, in both regenerating (fish) and nonregenerating (rat) central nervous systems, crush injury of optic nerve is followed by the disappearance of astrocytes from the site of injury. In fish, the injury site is subsequently repopulated by astrocytes, in temporal and spatial correlation with axonal growth across it (8)(9)(10). In the rat, the slow repopulation of the injury site by astrocytes is in apparent correlation with the failure of the regrowing injured axons to traverse it and may signify the astrocyte failure to express growth supportive elements.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data from other fish species, including hagfish and lamprey, indicate differences in IF protein expression programs between fish and terrestrial vertebrates (Alarcon et al 1993;Glasgow et al 1994;Arenas et al 1995;Merrick et al 1995;Zaccone et al 1995;Groff et al 1997). So far, however, many IF protein studies of fish have been limited to a single specialized organ or tissue (e.g., Pankov et al 1986;Giordano et al 1989;Frail et al 1990;Druger et al 1992;Cohen et al 1993;Koch et al 1994;De Guevara et al 1994;Byrd and Brunjes 1995;Bodega et al 1995;Cordeiro et al 1996;Tsai 1996). Comprehensive immunocytochemical keratin surveys are available for several teleosts (e.g., Thompson et al 1987;Bunton 1993;Ainis et al 1995;Groff et al 1997); however, these studies lack biochemical details of the IF proteins.…”
Section: Introductionmentioning
confidence: 99%